KESIAPAN FASILITAS KESEHATAN PRIMER SWASTA KLINIK PRATAMA DALAM PELAYANAN TBC - Halawa, Serius; Ritonga, Imelda Liana (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Tuberculosis (TB) is a type of infectious disease which is one of the ten main causes of world health problems because it has negative impacts including death. The aim of this research is to find out how prepared the private primary health facility Pratama Clinic is for TB services. The research method used is descriptive qualitative research. The location of this research was carried out at four Pratama Clinics in the working area of the Terjun Community Health Center, Paya Pasir Village, Medan City. This research was carried out from March to August 2023. The number of participants in this research were 8 health workers who worked at the Pratama Clinic. Research data was collected through in-depth interviews with participants and analyzed thematically. The research results consist of 5 (five) themes, namely: (1) tuberculosis examinations have been carried out, but sputum examinations are still carried out at community health centers, (2) examination results take a long time due to the lack of equipment, (3) tuberculosis training is only attended by personnel certain health conditions and (4) patients do not return to the clinic to get tuberculosis results because the patient's understanding of tuberculosis is still lacking. The conclusion of this research is that the Pratama clinic is ready to treat TB patients and the clinic only provides pots for suspected sputum from patients, the limited sputum examination tools mean that you have to wait for the results within two to three days, the Pratama clinic has already attended training but those who do training only certain people and patient understanding about tuberculosis is still lacking.